Virtual Education Audiovisual Model of the New Normal Adaptation toward Campus Community Behaviors in Preventing the Spread and Transmission of Covid-19 - Sudirman Sudirman; Suharto Suharto; Nina Indriyawati (Poltekkes Kemenkes Semarang, 2022)
Background: the number of confirmed or positive cases of Covid-19 has increased significantly. However, the behavior and awareness of the community to work together to fight Covid-19 is still low. Education through various methods and media is an important component in adapting to new normal life. The campus community is expected to be a pioneer in preventing the spread and transmission of covid-19. Purpose: to develop a virtual education audiovisual model for adapting to new normal, and to assess its effect on the behavior of the campus community in preventing the spread and transmission of covid-19.Methods: the research designs used Research and Development (RD) and true - experimental design with control group. The 306 respondents were recruited in this research by randomized. Data collection using a questionnaire assisted by the google form program. Data were analyzed using the Wilcoxon test and the Mann Whitney test.Results: the results of the study showed that the virtual education audiovisual model with adaptation to new normal had an effect on increasing knowledge (p 0.0001), increasing positive attitudes (p 0.0001), and actions (p 0.0001) of the campus community. The total mean score of campus community behavior was in the range 0-75, before treatment was 65.69 (SD + 5.99) and after 73.52 (SD + 2.68) with a difference of 7.83 (p 0.0001).Conclusion: the virtual education audiovisual model of the new normal adaptation had improved the behavior of the campus community in preventing the spread and transmission of covid-19.